Escherichia coli glucuronylsynthase: an engineered enzyme for the synthesis of β-glucuronides - Wilkinson, Shane M.; Liew, Chu W.; Mackay, Joel P.; Mohd. Salleh, Hamzah; Withers, Stephen G.; McLeod, Malcolm D. (American Chemical Society, 2008)
The glycosynthase derived from E. coli β-glucuronidase catalyzes the glucuronylation of a range of primary, secondary, and aryl alcohols with moderate to excellent yields. The procedure provides an efficient, stereoselective, and scalable single-step synthesis of β-glucuronides under mild conditions.